CHEMISTRY IN NON-SCHOOL SPACES: OBSERVATION IN A SETTLEMENT IN THE EXTERIOR SOUTH OF BAHIA - Martins Ribeiro, Alessandro; de Oliveira Franco, Tiago; Miranda Lago, Vivian (Journal of Interdisciplinary Debates, 2022)
INTRODUCTION: Access to basic education has advanced a lot with educational policies that have made possible disciplines such as chemistry present in the environment where we live in the school routine. OBJECTIVE: The aim was to observe from the point of view of students in the 9th year of an elementary school in a resident settlement in the extreme south of Bahia. MATERIALS AND METHODS: RESULTS: Through a descriptive and qualitative observation research, carried out during the application of the curricular component of chemistry. It was observed that in their homes, it is present in substances such as water, chlorine, soap, and inorganic foods, animal husbandry, chemistry is part of the balance of development, in the community, electricity, television and radio, of cooking gas and wood stoves, as well as the balance in minimizing zoonoses that affect animal and human life. CONCLUSION: Therefore, chemistry involves much more than complex concepts and calculations, it is a collection of the whys of reactions, phenomena within the daily life of each student.